The development of enrichment book of chemistry in our body based on augmented reality and its influence on chemistry literacy and scientific attitude of high school student - Basri, Muhammad Fikri M; Ikhsan, Jaslin (Jurnal Pendidikan Kimia, 2024)
This research aims of this research is to obtain produce enrichment book of chemistry in our body based on augmented reality which can display the 3D shape of molecular shape and chemical bonds developed from macromolecular materials that are suitable for increasing student chemical literacy and scientific attitude. This development research uses a 4D model developed by Thiagarajan which consists of stages Define, Design, Development, and Disseminate. The trial was carried out on 1 limited test class and 2 wide test classes (1 experimental class and 1 control class) of XII Science students at Senior High School of Angkasa Adisutjipto. The results of the research show that: 1) Enrichment book of chemistry in our body based on augmented reality that have been developed have very decent quality by media and materials validators; 2) the practicality response are included in the "Very Good" category with the average score of the percentage of ideals obtained of 88.62%; 3) the students response are included in the "Very Good" category with the average score of the percentage of ideals obtained in the limited trial of 81.21% and extensive trial of 84.39%; 4) the product are effective in increasing students chemical literacy and scientific attitude with the MANOVA test which obtained a significance value of 0.001; 5) the product are effective in improving students' chemical literacy with the MANOVA test which obtained a significance value of 0.006; 6) the product are effective in increasing students' scientific attitudes with the MANOVA test which obtained a significance value of 0.006.